Using New Instruments of Clustering Policy in the Health Care System. The Case of Poland - Romaniuk, Piotr; Holecki, Tomasz; Woźniak-Holecka, Joanna (Frontiers in Pharmacology, 2016)
The issue of clusters as a form of organization of market entities has recently attracted an increasing attention of health care management theoreticians and practitioners. In our opinion the existing theoretical basis gives a foundation for considering clusters as a source of potential for increasing the effectiveness of health policy and health care organizations. It can be assumed that in case of health care clusters there is a possibility of interregional diffusion of innovation, based on ventures undertaken on the health care market, increasing not only the potential of the entities in the cluster, but also of its surroundings and subcontractors. It is possible to realize the idea of a flexible health care implemented regionally with the use of modern techniques of communication, knowledge transfer and high specialization. Nonetheless, in case of Poland the potential of clustrification remains untapped, being characterized by a limited actions of public and private bodies, marginal role of non-profit sector organizations and limited engagement of R&D sector. This is because a general distrust in the cluster formula, and the lack of relevant knowledge among local officials and health business leaders. For this reason the process of clustrification among health care entities requires external support through the increased efforts to create a system of legal and tax preferences for cluster initiatives and provision of organizational support in terms of know-how, targeted particularly at bodies and individuals, who may act as cluster leaders.